2015
DOI: 10.1007/s12011-015-0554-6
|View full text |Cite
|
Sign up to set email alerts
|

Selenium Induces an Anti-tumor Effect Via Inhibiting Intratumoral Angiogenesis in a Mouse Model of Transplanted Canine Mammary Tumor Cells

Abstract: Selenium (Se) has been widely reported to possess anti-tumor effects. Angiogenesis is the formation of new blood vessels and is required to supply oxygen, nutrients, and growth factors for tumor growth, progression, and metastasis. To explore whether the anti-tumor effect of Se was associated with angiogenesis in vivo, we studied the effects of sodium selenite (Sel) and methylseleninic acid (MSA) on tumors induced by canine mammary tumor cells (CMT1211) in mice; cyclophosphamide (CTX) served as a positive cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 49 publications
1
17
0
Order By: Relevance
“…In contrast, the remaining selenocompounds (2-7) were non-selective, with the exception of 4 on Colo 320 MDR cells (SI = 2.3, slightly selective). None of the four reference compounds evaluated (12)(13)(14)(15) showed cytotoxic activity in any of the cell lines assayed: the human colon adenocarcinoma cells (Colo 205 and Colo 320, Table 3), the non-tumoral MRC-5 cells (Table 3) and the mouse T-lymphoma cells (PAR and MDR, data now shown). In the case of the pair selenoanhydride (1) -phthalic anhydride (12), results highlight the importance of the selenium atom to the biological activity.…”
Section: A R T I C L E I N F O Abstract Abcb1 (Atp Binding Casmentioning
confidence: 95%
“…In contrast, the remaining selenocompounds (2-7) were non-selective, with the exception of 4 on Colo 320 MDR cells (SI = 2.3, slightly selective). None of the four reference compounds evaluated (12)(13)(14)(15) showed cytotoxic activity in any of the cell lines assayed: the human colon adenocarcinoma cells (Colo 205 and Colo 320, Table 3), the non-tumoral MRC-5 cells (Table 3) and the mouse T-lymphoma cells (PAR and MDR, data now shown). In the case of the pair selenoanhydride (1) -phthalic anhydride (12), results highlight the importance of the selenium atom to the biological activity.…”
Section: A R T I C L E I N F O Abstract Abcb1 (Atp Binding Casmentioning
confidence: 95%
“…The CMT1211 and CMT7364 canine mammary tumour cell line were provided by Professor Degui Lin of China Agricultural University and have been used in the study of canine mammary tumours 17,18 . Human HEK293 cells were purchased from American Tissue Culture Collection (ATCC, Rockville, MD).…”
Section: Methodsmentioning
confidence: 99%
“…; Li et al . ). However, although several studies have reported on the expression of angiogenesis‐related genes in canine tumours, few studies have compared the expression profiles of angiogenesis‐related genes in normal and tumour tissues.…”
Section: Introductionmentioning
confidence: 97%
“…In the field of veterinary oncology, the importance of angiogenesis in tumour progression has been recognised (Restucci et al 2003;Millanta et al 2006;Yonemaru et al 2006;Camacho et al 2014), and several therapies targeting tumour angiogenesis are being used for some tumour types (Scharf et al 2013;Li et al 2016). However, although several studies have reported on the expression of angiogenesisrelated genes in canine tumours, few studies have compared the expression profiles of angiogenesisrelated genes in normal and tumour tissues.…”
Section: Introductionmentioning
confidence: 99%